Calidad de vida en cuidadores de pacientes con lesión medular. Una revisión documental. (2020)
Spinal cord injury (SCI) is defined as a pathological process that generates alterations in neurological function that can be motor, sensitive or autonomic, this leads to the need for a caregiver to assume the care tasks, supplying the basic needs of the patient at the same time as Own. The objective of this research is to analyze the impact on the quality of life of caregivers of patients with spinal cord injury. The research design is non-experimental, cross-sectional, descriptive, with a quantitative approach, which allowed collecting the information through a statistical analysis and later checking the results with the stated objectives, finally it is based on the empirical-analytical paradigm. It was identified that depending on the type of injury, an overload is also generated that is directly proportional to its negative impact on the physical and psychological dimension of the caregivers' quality of life. The need to generate interventions directed at this type of population in particular arises.